Measuring system for testing electrical parameters of EMCCDs of various formats - Viacheslav Zabudsky; Oleksandr Golenkov; Oleg Rikhalsky; Vladimir Reva; Sergij Korinets; Sergey Dukhnin (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
This article describes the developed equipment that allows measuring the photoelectrical parameters of multielement photodetectors, specifically various formats of EMCCD (electron multiplying charge-coupled device) chips. The authors present the measuring techniques and test results on dark currents, output amplifier sensitivity, charge transfer efficiency, charge capacity and other parameters. The studies were conducted, both on the wafer and in the body, on samples of the following formats: 576×288, 640×512, 768×576, 1024×1024, and 1280×1024.